The N-terminal region of influenza virus polymerase PB1 adjacent to the PA binding site is involved in replication but not transcription of the viral genome - Binh, Nguyen T.; Wakai, Chitose; Kawaguchi, Atsushi; Nagata, Kyosuke (Frontiers in Microbiology, 2013)
The influenza virus genome forms viral ribonucleoprotein (vRNP) complexes with nucleoprotein and viral RNA-dependent RNA polymerases (RdRp), PB1, PB2, and PA subunits. The vRNP complex catalyzes both genome replication and transcription reactions. PB1 contains the motifs highly conserved among RdRps and functions as a catalytic subunit of RdRp. The N-terminal region of PB1 between amino acid (a.a.) positions 1–83 contains both putative vRNA and cRNA promoter binding sites and a PA binding site. However, except for the PA binding site, the crystal structure and the function of the N-terminal region of PB1 are poorly understood. Here, we have examined the functional structure of the N-terminal region of PB1. The regions between a.a. positions 1–50 are highly conserved between influenza A and B viruses, but amino acids at positions 16, 27, and 44 are different between two viruses. To elucidate the functional importance of these amino acids in replication and transcription of the viral genome, we generated viruses containing mutations at these positions by reverse genetics and examined replication and transcription activities of these mutants. We found that a.a. positions 27 and 44 are responsible for the viral replication activity but not transcription activity.